Exploring nursing students’ reality shock and professional behavioral development in clinical practice: a hermeneutic phenomenological study - Cui, Feifei; Jin, Yundan; Wang, Rongting; Zhang, Jingya; Jin, Congying; Xu, Fangju; Yang, Songping; Yao, Meiqi; Han, Shijian; He, Hangying (Frontiers in Medicine, 2025)
BackgroundThe reality shock experienced by nursing students in clinical practice has attracted considerable attention. However, existing studies largely focus on quantitative analysis and overlook the depth of individual experiences.ObjectiveThis study adopts a qualitative research method and utilizes hermeneutic phenomenology to examine in depth the reality of the shock faced by nursing students during clinical practice, to demonstrate its impact on the development of professional behavior and to provide empirical evidence to improve nursing education.MethodsA qualitative research method was adopted involving 30 nursing students completing a 32-week clinical internship at a tertiary hospital in Jinhua City. The subjects participated in focus group interviews conducted in three groups to collect information about their learning experiences during the internship. Wiklund’s hermeneutic-phenomenological approach was used to analyze and interpret the data.FindingsFrom the learning experiences of nursing students in clinical practice, three main themes of “promoting professional nursing behavior” were summarized: (1) Guidance from clinical instructors: The influence of preceptors’ words and actions on students’ professional behaviors; (2) Inspiration from clinical nurses: Observing experienced nurses enhances students’ professional identity; (3) Learning from real-life cases: Clinical cases help students understand the core values of nursing.ConclusionNursing students face emotional challenges and cognitive changes during clinical practice. Clinical instructors should instill positive energy in these students through professional behavior. They should encourage students to observe, analyze, and reflect on the exemplary words and actions of clinical nurses and to obtain authentic feedback through patient interactions to refine their professional behavior. This study can serve as a valuable reference for clinical teachers in supervising nursing students entering clinical practice for the first time and helping them develop their professional nursing behavior.